Epidemiology of malaria in the Taabo health and demographic surveillance system, south-central Côte d'Ivoire. (December 2016) - Bassa, Fidèle; Ouattara, Mamadou; Silué, Kigbafori; Adiossan, Lukas; Baikoro, Nahoua; Koné, Siaka; N'Cho, Moussan; Traoré, Mahamadou; Bonfoh, Bassirou; Utzinger, Jürg; N'Goran, Eliézer
Abstract Background A deep understanding of the local epidemiology of malaria is essential for the design and implementation of setting-specific control and elimination efforts. In Côte d'Ivoire, new initiatives are underway to reduce the burden of malaria, which requires high-quality longitudinal data. The epidemiology of malaria was studied in the Taabo health and demographic surveillance system (HDSS) in south-central Côte d'Ivoire and implications for control are discussed. Methods Two cross-sectional surveys were carried out in the rainy season of June/July in 2010 and 2011. Inhabitants of approximately 7 % of randomly selected households in the Taabo HDSS were invited to participate. People were clinically examined, ear temperature was measured and spleen size determined. Finger-prick blood samples were collected and subjected to a rapid diagnostic test (RDT). Additionally, thick and thin blood films were prepared on microscope slides and diagnosed under a microscope forPlasmodium infection and parasitaemia. Haemoglobin (Hb) level was determined using a HemoCue device. Results A total of 1187 and 1264 people in 2010 and 2011, respectively, had complete data records. The prevalence ofPlasmodium infection was 46.0 % in 2010 and 56.6 % in 2011, owing to a statistically significant difference (p  < 0.05). Males showed a higherPlasmodium infection prevalence than females (49.6 and 62.8 % versus 42.6 and 51.2 %; respectively, in 2010 and 2011; bothp  < 0.05). The highest malaria prevalence was observed among infants and young children (aged ≤9 years). The risk ofPlasmodium infection was significantly higher in villages compared to small hamlets and urban settings (p  < 0.05). Fever, Hb level and splenomegaly were associated with parasitaemia. Conclusion Malaria is highly endemic in the Taabo HDSS in south-central Côte d'Ivoire with considerable spatial heterogeneity ofPlasmodium infection. There is a pressing need to scale-up control interventions against malaria.